Genesis and Significance of Hegel’s Phenomenology of Spirit - Pagano, Maurizio (Religija ir kultūra, 2013)
In this paper, I first of all present the evolution of the young Hegel’s thought. The reflection on the divisions and tensions of modern society and culture motivates him to raise the question about a possible reconciliation, and to research a principle that is able to ground this reconciliation itself. That’s how the theory of the Absolute is born, and on this basis Hegel later develops the project of his Phenomenology of Spirit. The main topic of this work is the path through which common conscience elevates itself to the absolute knowledge by going through the different steps of experience. In the last part of the paper, I describe more generally the meaning of the notion of “spirit” in Hegel’s later thought and the legacy it left.